(untitled) (Web of Teachers: Inderscience Research, 2025)
This article highlights the methodological foundations and practical methods for developing auditory perception in children with visual impairments. It analyzes the possibilities of using auditory analyzers as a compensatory tool for blind and visually impaired children, the role of hearing in perceiving the environment, and effective systems of special correctional activities.